TACTICAL DECISION MAKING IN TERMS OF BUYING FROM SUPPLIER OR SELF-PRODUCING USING RELEVANT COST IN â€œMISS Aâ€ FASHION BUSINESS - Tejo, Meliyana Prasetyo (Accounting Department,, 2015)
This research discusses about tactical decision making using relevant cost analysis as a basis for make-or-buy decision making in MISS A Company. This study aims to determine the decision that should be made by MISS A in order to grow and face the fierce rivalry in the fashion industry. MISS A company faces options to keep buying from supplier or start building home industry and self-producing. This study uses documentation, interview, and observation to collect the data. The method used in this study is relevant cost analysis which compares relevant costs and benefits in the decision making process. The findings of this study indicate that relevant cost analysis can be used in short-term decision making. The company should also consider the long-term impacts of the decisions made. The best decision for the company to make is to keep buying from supplier for Bangkok dresses line and to self-produce for local tops, Bangkok tops, and Hongkong dresses lines. This study is limited and conducted as short-term decision making based on the companyâ€™s internal data between 2012 and 2013.Â Keywords: relevant cost analysis, make-or-buy, alternative, decision making, short-term decision